A.F.D / Nur Nadhirah Abdul Karim …[et al.] - Abdul Karim, Nur Nadhirah; Zainor, Nur Athirah Munirah; Abd Razak, Norfarhana; Mohd Aris, Syamimi Syahirah; Md Yazid, Siti Aisyah (2019)
Automated food distributor (AFD) was designed to distribute food to dairy animal using an automatic system which is conveyor belt and mixer that functioning to distribute and process animal's food. This process also controlled by a timer to set up time of foods distribution to the cell of the shelter. The inspiration comes from the interviewed with dairy farmers that give students an idea to do innovation in term of work efficiency and quality in terms of food distribution concept and food processing. The idea came from the research conducted by the publication, online portal, and the dairy farmer themselves. The approach was decided on the basis of all the questionnaire, interview and analysis from the problems faced by the dairy farmer. Automated Food Distributor (AFD) helps to efficiently conduct the feeding time, minimizing the number of workers, thus also reducing costs and ultimately saving the workers ' time and energy. Food time became efficient because the farmer simply had to put the grass in the mixer and mix the grass in the pallet. The mixture would then collapse into the tank on the conveyor belt. Until the livestock, the conveyor must shift and stop. The timer can be programmed and changed by the farmers as they wish. This system will continue to reduce the amount of resources required and save time as well.